5-Aryl-1,3,4-oxadiazol-2-ylthioalkanoic Acids: A Highly Potent New Class of Inhibitors of Rho/Myocardin-Related Transcription Factor (MRTF)/Serum Reponse Factor (SRF)-Mediated Gene Transcription as Potential Antifibrotic Agents for Scleroderma - Kahl, Dylan J. (J Med Chem, 2019)
Through a phenotypic high throughput screen (HTS) using a serum response element luciferase (SRE.L) promoter, we identified a novel 5-aryl-1,3,4-oxadiazol-2-ylthiopropionic acid lead inhibitor of Rho/MRTF/SRF-mediated gene transcription with good potency (IC(50) = 180 nM). We were able to rapidly improve the cellular potency by 5 orders of magnitude guided by sharply defined and synergistic SAR. The remarkable potency and depth of the SAR, as well as the relatively low molecular weight of the series, suggests, but does not prove, that binding to the unknown molecular target may be occurring through a covalent mechanism. The series nevertheless has no observable cytotoxicity up to 100 μM. Ensuing pharmacokinetic optimization resulted in the development of two potent and orally bioavailable anti-fibrotic agents that were capable of dose-dependently reducing connective tissue growth factor (CTGF) gene expression in vitro as well as significantly reducing the development of bleomycin-induced dermal fibrosis in mice in vivo.